Study the Effect of Adding Materials (Calcine Powder Styropor Granules and Straw) on the Compressive Strength for Material Polyurethane - Rawad Shakohe (Tishreen University, 2023)
The research aims to study the effect of adding different materials to polyurethane on the compressive strength before and after adding the materials. Samples of this material were made with different percentages of polyisocyanate and polyols, (which are organic compounds derived from the oil that) they make up. Where the following materials were added( Straw,calcinepowder,and styrepor granules)in order to study thecompressive strength of polyurethane,where the compressive strength of samples of this insulation material was measured at different ratios of polyisocyanate and polyol with and without additives for,another material. thermal insulation material of polyurethane with a compressive strength of 640 (KN/m2), consisting of 74%  polyisocyanates and24%  polyols by weight, with the addition of calcine powder at a rate of 2 % .